The Link Between Ultra-Processed Food Consumption and Adolescent Mental Health Disorders: A Systematic Review - Karina Muthia Shanti; Sugeng Iwan Setyobudi; Irma Afifa (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2026)
Background: The increasing prevalence of mental health problems among adolescents underscores the importance of identifying contributing factors, one of which may be dietary patterns, particularly the rising consumption of ultra-processed foods. This study aims to explore the association between ultra-processed food consumption and mental health issues in adolescents.Methods: This study conducted in systematic literature review. A comprehensive search was conducted following PRISMA guidelines, using the Scopus database to identify studies published between 2020 and 2025. Inclusion criteria focused on observational studies involving adolescents aged 10–19 years, examining the relationship between ultra-processed food intake (classified according to the NOVA system) and mental health outcomes.Results: Seven studies (n = 284,507) met the inclusion criteria, with six showing an increased risk of mental health problems linked to higher ultra-processed food consumption. One study revealed a bidirectional relationship, where academic stress was associated with increased fast food consumption.  Conclusion: Most included studies indicate that higher ultra-processed food consumption is associated with increased odds or risk of mental health problems among adolescents. In addition, one study reported a possible reverse pathway, suggesting that academic stress may be linked to greater fast-food consumption. Further longitudinal and mechanistic research is needed to clarify the causality and directionality, before specific intervention strategies can be recommended.